EVALUASI PELAKSANAAN PROGRAM PEMBERDAYAAN DESA (PPD) DI KABUPATEN ROKAN HULU - Makmur (Fakultas Ekonomi Universitas Pasir Pengaraian, 2015)
The researchisis an evaluational study on the empowerment of Program village Performing atRokan Hulu Regency Upstream, it was performed on december 2013 until May 2014. Te aims of thisresearch is subject know the empowerment Program village performing at Village Rambah, and toanalyse the credit channelizing by UED – SP . This research wasa case study on Economic EffortSaving and LendingKumu Jaya Village Rambah, with 60 persons, used random simpling. From thefinding, it was found that the program has been applied well as the rules determined.